# Problem: Given the following dataFe2O3 (s) + 3 CO (g) → 2 Fe (s) + 3 CO2 (g)         ΔH° = -23 kJ3Fe2O3 (s) + CO (g) → 2 Fe3O4 (s) + CO2 (g)     ΔH° = -39 kJFe3O4 (s) + CO (g) → 3 FeO (s) + CO2 (g)            ΔH° = 18 kJcalculate ΔH° for the reactionFeO(s) + CO(g) → Fe(s) + CO2(g)

###### FREE Expert Solution

Hess’s Law →  sum of ΔH° of individual steps is equal to ΔH° of overall reaction (ΔH°rxn)

Reaction 1: Fe2O3 (s) + 3 CO (g) → 2 Fe (s) + 3 CO2 (g)         ΔH° = -23 kJ

Reaction 2: 3 Fe2O3 (s) + CO (g) → 2 Fe3O4 (s) + CO2 (g)     ΔH° = -39 kJ

Reaction 3: Fe3O4 (s) + CO (g) → 3FeO (s) + CO(g)            ΔH° = 18 kJ

Overall reaction: FeO (s) + CO (g) → Fe(s) + CO2 (g)         ΔH°rxn = ??

For (3): FeO → opposite side, different coefficient

Modify: Invert/reverse (3)

3FeO (s) + CO(g)    →     Fe3O4 (s) + CO (g)     ΔH°3,rev = -18 kJ (sign changes)

To get overall eqn:

[3FeO (s) + CO(g)    →     Fe3O4 (s) + CO (g)     ΔH°3,rev ] x 2

[Fe2O3 (s) + 3 CO (g) → 2 Fe (s) + 3 CO2 (g)        ΔH°1 ] x 3

2 Fe3O4 (s) + CO2 (g) → 3 Fe2O3 (s) + CO (g)     ΔH°2,rev

98% (135 ratings)
###### Problem Details

Given the following data

Fe2O3 (s) + 3 CO (g) → 2 Fe (s) + 3 CO2 (g)         ΔH° = -23 kJ

3Fe2O3 (s) + CO (g) → 2 Fe3O4 (s) + CO2 (g)     ΔH° = -39 kJ

Fe3O4 (s) + CO (g) → 3 FeO (s) + CO(g)            ΔH° = 18 kJ

calculate ΔH° for the reaction

FeO(s) + CO(g) → Fe(s) + CO2(g)